Reuse of Molecules for Glioblastoma Therapy - Abigail Koehler; Aniruddha Karve; Pankaj Desai; Jack Arbiser; David R. Plas; Xiaoyang Qi; Renee D. Read; Atsuo T. Sasaki; Vaibhavkumar S. Gawali; Donatien K. Toukam; Debanjan Bhattacharya; Laura Kallay; et al. (MDPI AG, 2021)
Glioblastoma multiforme (GBM) is a highly malignant primary brain tumor. The current standard of care for GBM is the Stupp protocol which includes surgical resection, followed by radiotherapy concomitant with the DNA alkylator temozolomide; however, survival under this treatment regimen is an abysmal 12-18 months. New and emerging treatments include the application of a physical device, non-invasive 'tumor treating fields' (TTFs), including its concomitant use with standard of care; and varied vaccines and immunotherapeutics being trialed. Some of these approaches have extended life by a few months over standard of care, but in some cases are only available for a minority of GBM patients. Extensive activity is also underway to repurpose and reposition therapeutics for GBM, either alone or in combination with the standard of care. In this review, we present select molecules that target different pathways and are at various stages of clinical translation as case studies to illustrate the rationale for their repurposing-repositioning and potential clinical use.